Mentoring as a motivational tool in scientific research - Lozano Lozano, Marilé (2020)
Addressing the topic of scientific research today is of great relevance since it is part of the backbone of professional training, to carry it out, we can use mentoring as a tool to motivate and drive to strengthen scientific research. This research set out the following objectives: to determine the relationship between mentoring as a motivational tool and scientific research and to understand the experiences of Norbert Wiener University teachers in the mentoring process to develop as researchers, a mixed approach, Descriptive correlational concurrent design. The sample was made up of teachers from the aforementioned institution, for data collection two questionnaires and a semi-structured interview were used, for data treatment the SPSS version 23 and Atlas ti version 7 software were used. between mentoring as a motivational tool and scientific research at the Norbert Wiener Private University. In relation to the experiences of the teachers interviewed, three main categories were obtained: The limitations to apply the Mentoring, from which the subcategories were obtained: Time, Investigative Policies, Economic Resources and infrastructure; the second category was Work teams as a strategy to develop research from which the subcategories emerged: multidisciplinary and Research networks at national and international level and finally the category The mentor profile, from which emerged: Research competencies, soft skills and commitment.